Dissolved organic Carbon Concerntration in an Oil Palm Plantation Planted on Tropical Peat - Wendy, Lim Wen (2016)
Dissolved organic carbon (DOC) is an important component in the environment especially in carbon cycle apart from the role it plays in water bodies and, hence, aquatic lives. As such, it have been widely studied in many countries especially temperate areas. Not much is known of DOC in tropical cOW1tries especially in Malaysia even in peat swamp areas where it is the major source ofcarbon storage as very few studies had been undertaken. A study on DOC was carried out from May 2013 until October 2014 in an oil palm plantation converted from a peat swamp area in South Selangor, Malaysia. The objectives of the study are to (i) determine the concentrations of DOC in groundwater and drainage channels within an oil palm plantation of different ages (ii) to find out the relationship between concentrations of DOC and oil palm ages, soil carbon, water quality parameters as well as with rainfall and groundwater level. Bimonthly samplings were undertaken on groundwater in piezometers installed at the oil palm blocks aged four, eight, twelve and fourteen years. Samplings were also undertaken in their respective nearby drains as well as drains within a one-year-old block. Water quality parameters including DOC were determined in the groundwater and drain water. Based on the 13 months ofsampling, the overall average DOC concentration recorded in this oil palm plantations was 60.78±4.51 mg L- t This amount is higher by 9.5% and 21 % respectively than those found in moderate disturbed peat swamp forest and severely drained disturbed peat swamp forest rivers in Sebangau River Basin, Central Kalimantan. Average groW1dwater DOC concentration in the 8 year-old oil palm block was the highest with 114.94±7.35 mg L- 1 and the lowest was at the 4 year-old oil palm area with IS.41±2.20 mg L- 1• For the drain water, average DOC concentration was the highest at the S-year-old palm area (I 09.24±1 0.04 mg L- 1) and lowest at tbe I-year-old block (24.12±9.59 mg L- 1). The overall average DOC concentration in both groundwater and drain water were signifIcantly different among the different ages of the oil palm.